The role of craftwork in achieving the social and physical independence of women in Algeria- Field study of workers in sewing craft - Wilayat Adrar - Raqani, Al - Zahraa; Laa‘la, Bokmish (Journal of Humanities & Social Sciences, 2018)
The present study analyses the fact of carftswoman. IT also defmes the contribution of the woman in the craftwork. Otherwis, this work talkes the improvement of the social stats of the women and independence from social beliefs and limits.Financially, the study defines the financial loyalty of the woman to others . IT also looks for the woman’s independence in work and production. The sample of the study is 80 female tailors. The study relies on the descriptive method, questionnaire and interview. The data are analyzed with the "spss programme, the averages and the coeffivènts corvelations between variables .According to the practical analyses the study, concluded that ther is a coutrast in the degree of the woman’s or financially. This is because: The social independence of the craftswoman increases and decreases according to her relationship with her society in addition to the impact of the social view towards the woman (challenges such as: megative beliefs, custons and traditions, jealousy and envy, the fenale privacy in the region, the movement of the craftswoman and her freedom to sell and prmote the product) The work of the craftswoman contributes to the improvement of her skills as a prodhcer. IT also satisfies her needs and the society’s needs. Despite of the fact, this contvibution is relative in comparison to her independence from the social loy alty. This refers to: the degree of dependency or others according to her needs, her movement inside and outside the region to attract custoners, the fluctuation of her income in the craftwork)
Keywords: craft work; craft woman; social independence; financial independence